Regional Political Leadership in Sweden and Finland: Do Institutional Conditions Affect Influence Over Regional Development? - Sundqvist, Emily (Scandinavian Journal of Public Administration, 2021)
Leading regional development is a key task for regional council representatives. Regional councils are responsible for fostering self-sufficient strategic development in cooperation with a range of stakeholders, including businesses, universities, NGOs and public authorities. However, little attention has been paid to investigating the conditions for regional political leadership, and the relationship between the regional councils’ institutional capacity and politicians’ perceived influence on regional development is somewhat unexplored. The aim of this article is thus to study whether institutional conditions affect the perceived influence of politicians. A comparison is made in three types of regional councils in Sweden and Finland, employing a survey of 930 representatives. These councils share a similar responsibility for regional development, but they operate within different institutional conditions. Findings show that institutional conditions matter to some extent, with a higher institutional capacity strengthening the assembly’s position and increasing perceived influence at an individual level, though not necessarily increasing the regional councils’ possibilities to exercise strategic leadership. Moreover, regional councils with a higher institutional capacity are more autonomous organisations, while a lower degree of authority makes the regional councils more dependent on the state level.